Industrial training report: Johor Port / Nur Afini Othman - Othman, Nur Afini (Faculty of Business and Management, 2025)
This report is the summarize of my internship. The main purpose is to gain more knowledge and explore more experience that I can as well as I will acquire my knowledge during my studies. This report consists of my profile, company profile where included logo and history of establishment, vision, mission, objective and goal. Other than that, the company profile also includes organisational structure and services. Besides, in this report, I will present the training reflection which includes all the details and all of the memories. The main goals of the internship were to enable students to cultivate and improve specific skills relevant to their field of study and career aspirations, as well as to provide them with hands - on experience in a professional environment where they could apply world work scenarios. Through practical involvement,mentor guidance and engagement in a wide range of duties. Hence, the students effectively achieved these objectives. The signifcance of efficient communication and adaptability in a working environment was higlighted through collaboration wity various teams and ability to adjust to varied duties. I worked in Procurementt and Central Store Department, which gave me the chance to learn on how to manage purchase orders of Johor Port Berhad, contracts, and tender documents. In which it can enhanced my attention to detail and organizational skills. In addition, I collaborated with cross-functional teams to address procurement-related issues and contributed to improving supplier relationships by assisting in communication and resolving queries efficiently. In conclusion, The internship provided me with a comprehensive understanding of supply chain management principles, vendor management processes, and the importance of cost control in achieving operational efficiency. Furthermore, I developed critical soft skills, such as teamwork, problem-solving, and effective communication, which are essential for success in the procurement field. Overall, the internship at Johor Port Berhad's Procurement Department was an enriching experience that allowed me to apply my academic knowledge in a professional setting while building a solid foundation for a career in procurement and supply chain management.